PENGARUH ATTRIBUTES CONSUMER SATISFACTION TERHADAP STORE LOYALTY HARTONO ELEKTRONIK BUKIT DARMO SURABAYA - HADDY, KENNY (Kajian Ilmiah Mahasiswa Manajemen, 2012)
This study aims to examine and analyze influence of attributes related to the product, attributes related to the service and attributes related to the purchase to store loyalty. The benefits from this study is to provide sugesstions to marketers within the company as a basis for using the attributes to gain store loyalty in the minds of consumers. Variables in this study consisted of independent variable and dependent variable. Independent variable consisted of attributes related to the product, attributes related to the service and attributes related to the purchase. While dependent variable consisted of store loyalty. Sampling technique used in this study is purposive sampling which means that sampling is done with the selection of respondent accordance with predetermined characteristics. While the analysis techniques used are multiple linear regression analysis model. Hypothesis in this study indicate that, H1: attributes related to the product has a positive influence on store loyalty, H2: attributes related to the service has a positive influence on store loyalty, H3: attributes related to the purchase has a positive influence on store loyalty. The results in this study indicate that attributes related to the product, attributes related to the service and attributes related to the purchase has positive influence on store loyalty.